A role for adeno-associated viral vectors in gene therapy - Renata dos Santos Coura; Nance Beyer Nardi (Genetics and Molecular Biology, 2008)
Gene therapy constitutes a therapeutic intervention based on modification of the genetic material of living cells, by correcting genetic defects or overexpressing therapeutic proteins. The success of gene therapy protocols depends on the availability of therapeutically suitable genes, appropriate gene delivery systems and proof of safety and efficacy. Recent advances on the development of gene delivery systems, particularly on viral vectors engineering and improved gene regulatory systems, have led to marked progress in this field. Although the available vector systems can successfully transfer genes into cells, the ideal delivery vehicle has not been found. In this context, adeno-associated virus vectors (AAV) are arising as a promising tool for a wide range of applications, due to a combination of characteristics such as lack of pathogenicity and immunogenicity, wide range of cell tropism and long-term gene expression. Since its isolation, the biological properties of the adeno-associated virus have been increasingly understood, improving our ability to manipulate and use it as a safe and efficient gene therapy vector of wide spectrum. In this work, we review the bases of gene therapy, main types of gene transfer systems and basic properties and use of AAV vectors.